PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP MINAT BELI ULANG PADA RESELLER PRODUK FASHION MUSLIMAH DI HIMALAKAI GROUP KOTA CIMAHI - Siti Mariam; Rini Handayani (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
The purpose of this study is to determine and analyze the influence of product quality and promotion on repurchase interest among resellers of Muslim fashion products at Himalakai Group, Cimahi City. The research method used is quantitative with a descriptive and verificative approach. Data were obtained through questionnaires distributed to 94 respondents who are resellers of Himalakai Group and analyzed using multiple linear regression with the help of statistical software. The results show that product quality has a positive and significant effect on repurchase interest with a contribution of 17.2%, while promotion has a positive and significant effect with a contribution of 35.6%. Simultaneously, product quality and promotion have a positive and significant effect on repurchase interest with a contribution of 51.8%, while the remaining percentage is influenced by other factors outside this research. The study concludes that the better the product quality and the more effective the promotion strategy implemented, the higher the reseller repurchase interest in Himalakai Group’s Muslim fashion products. These findings are expected to serve as a reference for the company in improving product quality and optimizing promotional strategies to strengthen reseller loyalty.